2013
DOI: 10.1021/la4006168
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Lipids Increase the Probability of Fluctuating Nanodomains in Mixed Membranes

Abstract: A ternary mixture model is proposed to describe composition fluctuations in mixed membranes composed of saturated, unsaturated, and hybrid lipids (with one saturated and one unsaturated hydrocarbon chain). The hybrids are line-active and can reduce the packing incompatibility between the saturated and unsaturated lipids. We introduce a lattice model that extends previous studies by taking into account the dependence of the interactions of the hybrid lipids on their orientations in a simple way. A methodology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 56 publications
5
75
1
Order By: Relevance
“…However, the cell membrane contains only a small amount of lipids with two saturated tails. Later work suggests that the hybrid lipids serve both as the bulk and the line agents [29, 30]. In a recent paper [26], Schick shows that the interaction between membrane curvature and membrane composition can produce a modulated phase; a phase that exhibits periodic order in the composition over long length scales.…”
Section: Application: Composition Fluctuationsmentioning
confidence: 99%
“…However, the cell membrane contains only a small amount of lipids with two saturated tails. Later work suggests that the hybrid lipids serve both as the bulk and the line agents [29, 30]. In a recent paper [26], Schick shows that the interaction between membrane curvature and membrane composition can produce a modulated phase; a phase that exhibits periodic order in the composition over long length scales.…”
Section: Application: Composition Fluctuationsmentioning
confidence: 99%
“…These raft-like domains grow several micrometers in size in giant unilamellar vesicles (GUVs) (7), while their mobility is preserved, whereas lipid domains in supported lipid bilayers are smaller but are largely immobile and do not form energy-minimized round shapes (10). Explanations for the size difference of lipid domains in native plasma membranes and model membranes range from the system's vicinity to a critical point (9), where density fluctuations prevail, over compositions with lipids having one saturated and one unsaturated fatty acid tail (11), coupling between composition and local membrane deformation (12)(13)(14), and the presence of the cortical cytoskeleton (15). It has been shown that attaching an artificial cytoskeleton made of actin or a tubulin homolog alters the shape and position of the ordered domains (16,17).…”
mentioning
confidence: 99%
“…http://dx.doi.org/10.1101/250944 doi: bioRxiv preprint first posted online Jan. 20, 2018; enough to be relevant physiologically and if so, what forces stabilize the domains at the nanoscopic range. This motivates a broad range of experimental and theoretical studies of model lipid membrane systems [12][13][14][15] . Several potential factors have been proposed, including entropic force and mechanical repulsion caused by the difference of the intrinsic curvature of different phases 1,16,17 .…”
Section: Introductionmentioning
confidence: 99%